Genetic Programming Theory and Practice IV
DOI: 10.1007/978-0-387-49650-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Applying Genetic Programming to Reservoir History Matching Problem

Abstract: History matching is the process of updating a petroleum reservoir model using production data. It is a required step before a reservoir model is accepted for forecasting production. The process is normally carried out by flow simulation, which is very time-consuming. As a result, only a small number of simulation runs are conducted and the history matching results are normally unsatisfactory.In this work, we introduce a methodology using genetic programming (GP) to construct a proxy for reservoir simulator. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…In oil recovery maximization, the objective is to find optimal water injection rates to increase the oil field production [14]- [16]. For history matching, the optimizer is looking for proper field model parameters (permeability, porosity, saturations, among others) which match numerical simulations and field measurements [17]- [19]. Finally, the GA are also used to decide optimal location of new wells taking into account future predictions of possible patterns and history data [20]- [22].…”
Section: Ga Methodsmentioning
confidence: 99%
“…In oil recovery maximization, the objective is to find optimal water injection rates to increase the oil field production [14]- [16]. For history matching, the optimizer is looking for proper field model parameters (permeability, porosity, saturations, among others) which match numerical simulations and field measurements [17]- [19]. Finally, the GA are also used to decide optimal location of new wells taking into account future predictions of possible patterns and history data [20]- [22].…”
Section: Ga Methodsmentioning
confidence: 99%
“…Instead, we used the simulator proxy model generated from our previous study [18] as a surrogate. In this way, this proof-of-concept study can be completed faster, avoiding the time-consuming computer simulation.…”
Section: A Case Studymentioning
confidence: 99%
“…Initially, we ran reservoir simulator on a small number of samples selected by uniform design [4] as we have observed that uniform-design samples are suitable for evolutionary systems to construct proxies [18]. These simulation data becomes the initial training data for the proxy population to train proxy models at the initial estimation phase.…”
Section: System Design and Implementationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaydani afirma que PG é uma poderosa ferramenta para reconhecer possíveis padrões entre conjuntos de entrada e saída, o qual pode ser aplicado para predizer parâmetros de reservatório. Outras pesquisas utilizam com sucesso PG nas áreas de: ajuste de histórico, criação de proxies de simuladores de reservatório e controle operacional de reservatório (YU, et al, 2007), (YU, et al, 2008), (FALLAH-MEHDIPOUR, et al, 2012 MAPE, que é uma medida de erro absoluto porcentual e o erro médio, que corresponde à média do valor absoluto dos erros.…”
Section: Sumáriounclassified